Analysis of morphological characteristics and phenetic relationship of ebony (Diospyros spp.) in Indonesia - Ridesti Rindyastuti; Lia Hapsari; Anjar Tri Wibowo (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Rindyaastuti R, Hapsati L, Wibowo AT. 2021. Analysis of morphological characteristics and phenetic relationship of ebony (Diospyros spp.) in Indonesia. Biodiversitas 22: 2738-2753. Diospyros L. (Ebenaceae) is an economically important genus that covers over 500 plant species. Members of this group are known to produce hard, dark, high-quality timbers known as ebony trees, while other members are known as persimmon trees. There is limited information on the morphological characters and phenetic relationship of this genus from Indonesian archipelago. In this work, we reported the phenetic clustering of 14 species of Indonesian Diospyros, based on plant habit, stem, leaves, and fruit characters, which was analysed using UPGMA and Jaccard similarity index. The phenetic dendrogram divided the 14 species of Diospyros into two main clusters which separating Subgen. Maba and Eudiospyros. Further, subgen. Maba was clustered into a single cluster while subgen. Eudiospyros was divided into 3 sub-clusters as sister groups. The clustering in Eudiospyros was supported by low SI and bootstrap value, demonstrating the high morphological variation of the subgenus. The sectional separation of Diospyros spp. was considered as paraphyletic. In general, our phenetic clustering exhibited suitability and relevancy with previous classification. Fruit size and trichomes are very important in this phenetic clustering, especially to form Eudiospyros subgenus. Fruit trichomes were also special characters related to biogeographical distribution following the Wallace line theory.